Evaluation of Mucopolysaccharidosis Patients Attending the Metabolic Consultation Clinic at The Central Child Teaching Hospital - Ali Dawood Salman; Hussein Abdulrassool Mahdi; Hussein Abdulkareem Noah (Academic Journal of Clinicians, 2025)
Background: Mucopolysaccharidoses are a class of uncommon lysosomal storage diseases characterized by multiorganic and severe symptoms. MPS occurs in different types over the world but has a low incidence. The most common variety of MPS differs among continents, indicating that it may be related to geography and social background. Aim of the study: To evaluate the mucopolysacaridoses patients attended the metabolic consultation clinic at the Central Child Teaching Hospital. Patients and method: A prospective observational study with an analytic element for all patients with mucopolysaccaridoses regularly attending the pediatric metabolic consulting clinic at the central child teaching hospital in Baghdad city over a period of 8 months from (1st of May till 26th of Dec. 2021). Results: This study enrolled 58 mucopolysaccharidoses patients aged between 3 months to 21 years. Males contributed for (56.9%). Among the studied group, positive consanguinity reported in (93.1%), family history of MPS in (58.6%). Type VI was the major type (46.6%) followed by IV, I and II. Coarse facial features were the most presenting signs among MPS I(87.5%) , II (71.4%) and VI (100%), while skeletal deformity was present mostly in type IV (100%). Corneal clouding is present in Type I (62%) and VI (81.5%) and less frequently in type IV (43.8%) and II (14.3%). Various neurological features were presented among MPS types I, II and VI. Delayed development was noted mostly in type I about (87.5%). Conclusion: Mucopolysaccharidoses are uncommon diseases. MPS-VI was the most frequent variant. The majority of the patients were born to conjoined parents. Coarse facies, hepatosplenomegaly, and dysostosis multiplex were all common clinical characteristics. Corneal clouding was most common in MPS-I, and heart abnormalities were found in MPS-I, III, and IV. Neurological involvement was observed in all MPS-II, III, and VI patients, but not in less than half of MPS-I individuals. Delayed development was noted in the majority of MPS type I.